Formation of Condyle-Like Structure after Treatment of Temporomandibular Joint Ankylosis: Literature Review and Long-Term Follow-Up of Two Patients - Orhan Güven (Case Reports in Medicine)
Treatment of ankylosis is one of the greatest challenges in temporomandibular joint (TMJ) surgery. To provide a satisfactory mouth opening, as well as normal jaw function, and to prevent reankylosis in the long term are the most important principles in the treatment of TMJ ankylosis. These functions have been attained in both of the presented patients in the long term. It is known that heterotopic bone formation is rare in the maxillofacial area, but rapid bone regeneration which reconstitutes a new condyle is rarer. The purpose of the presented paper is to reveal the existence of an inherent capability of the mandible, rapid bone growth of the ramus mandible, and reformation of a previously nonexisting condyle after resection of the ramus in patients with TMJ ankylosis. In this paper, two unusual cases of unexpected condyle-like structure formation after treatment of ankylosis were presented.